2018
DOI: 10.1177/0974686218769198
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Whistle-blower Protection Mechanism of Select Countries

Abstract: Whistle-blower protection mechanisms (WPMs) play a critically significant role in combating corruption through ethics, corporate governance and statutes. This article examines the essence of whistle-blower mechanism existing in the developed and developing countries in order to unearth the legislative structure of countries supporting the whistle blower mechanism and pursuit of ethical conduct for sound corporate governance. The article attempts to identify, evaluate and analyse the attributes of whistle-blowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Within this, few studies have compared the federal legislation with the state legislature and attempted to identify any states that offer better protection to whistleblowers than federal law currently provides (Goza, Tyner, & Johnson, 2014). Merely one paper under this theme has published in Indian journal where it has been revealed that legislation for whistleblower protection vary widely across nations with the US A delivering the best protection to whistleblowers trailed by Australian whistleblower protection laws and, then, South Africa; India, China and Indonesia lag considerably behind in having a sound whistleblower mechanism (Sharma, Kanojia, & Sachdeva, 2018).…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…Within this, few studies have compared the federal legislation with the state legislature and attempted to identify any states that offer better protection to whistleblowers than federal law currently provides (Goza, Tyner, & Johnson, 2014). Merely one paper under this theme has published in Indian journal where it has been revealed that legislation for whistleblower protection vary widely across nations with the US A delivering the best protection to whistleblowers trailed by Australian whistleblower protection laws and, then, South Africa; India, China and Indonesia lag considerably behind in having a sound whistleblower mechanism (Sharma, Kanojia, & Sachdeva, 2018).…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…On the contrary, Balakrishnan (2016) reports that the Malaysian Government has decided to retain and strengthen the application of sedition law, that could further impede the right to impart PSI in Malaysia. With regards to the protection of the whistleblower, Sharma et al (2018) work indicates that the UK, Canada and New Zealand whistleblower laws allow the employees to disclose wrongdoings direct to the public apart from the authorised body. The repealed or modification of the secrecy and sedition laws could further enable, protect and promote the right to impart PSI among the members of the public.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Whistle-blower protection is an important corporate governance tool for the protection of organizations' stakeholders and having a sound whistle-blower protection mechanism in place is an indicator of good corporate governance (Ffolkes-Goldson, 2015). In other words, having a robust whistle-blower mechanism is one of the most important devices for having good corporate governance (Sharma et al, 2018). Information provided by insiders can contribute to the goal of reducing illegal activities by capital market executives in countries.…”
Section: Introductionmentioning
confidence: 99%